F.C. Baur's synthesis of Bohme and Hegel : redefining Christian theology as a gnostic philosophy of religion - Simuț, Corneliu C. (Philosophy of Religion - World Religions, 2014)
In this book, Professor Simuț shows how Christian theology started to be understood as a Gnostic philosophy of religion in the thought of the 19th-century scholar F. C. Baur. Although Baur was seen traditionally as a theologian and biblical exegete, Simuț argues that he was in fact a philosopher of religion, and it was his philosophical reading of Christian theology that informed his biblical preoccupations. Specifically, Baur's perspective on Christian theology was heavily influenced by Jakob Böhme's esoteric theosophy and Hegel's religious philosophy in some key issues such as creation, Lucifer, dualism and the connection between spirit and matter coupled with that between philosophy and religion.